(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
Introduction. In recent years, the integration of digital technologies into education has transformed traditional teaching methods. One of the most promising approaches in this regard is gamification, which refers to the use of game elements and mechanics in non-game contexts to enhance learner motivation and engagement (Deterding et al., 2011). In English language teaching (ELT), gamification has gained significant attention due to its potential to create interactive and enjoyable learning experiences. For university students, who often struggle with motivation and self-regulation in language learning, gamification can serve as a tool that fosters autonomy, collaboration, and perseverance. This study explores the benefits of gamification in ELT, emphasizing its positive effects on learners’ individual engagement, motivation, and achievement.